Adaptive strong-field control of chemical dynamics guided by three-dimensional momentum imaging. - Ben-Itzhak, Itzik; Kling, M. F.; Bergues, B.; De Vivie-Riedle, R.; Carnes, K. D.; De, S.; Gaire, B.; Ablikim, U.; Andrews, P. R.; Jochim, B.; Siemering, R.; Zohrabi, M.; et al. (My University, 2013)
Shaping ultrafast laser pulses using adaptive feedback can manipulate dynamics in molecular systems, but extracting information from the optimized pulse remains difficult. Experimental time constraints often limit feedback to a single observable, complicating efforts to decipher the underlying mechanisms and parameterize the search process. Here we show, using two strong-field examples, that by rapidly inverting velocity map images of ions to recover the three-dimensional photofragment momentum distribution and incorporating that feedback into the control loop, the specificity of the control objective is markedly increased. First, the complex angular distribution of fragment ions from the nω+C2D4→C2D3++D interaction is manipulated. Second, isomerization of acetylene (nω+C2H2→C2H22+→CH2++C+) is controlled via a barrier-suppression mechanism, a result that is validated by model calculations. Collectively, these experiments comprise a significant advance towards the fundamental goal of actively guiding population to a specified quantum state of a molecule.
Keywords: Physical sciences; Physical chemistry; Atomic and molecular physics